METHOD EFFECT RECIPROCAL TEACHING COMMUNICATION SKILLS OF STUDENTS MATHEMATICAL SMP - Fratama, Eva Julia (Universitas Suryakancana, 2018)
This study aims to determine the extent of the influence method Reciprocal Teaching of themathematical communication skills of students SMP. The method used in the study is an experiment, with the research design is pretest-posttest control group. The population in this study were all students of secondary schools in Cianjur, while the sample were students of class VIII SMPN 1 Cikalongkulon randomly selected class. The instrument of this research is the description test communication skills as much as 5 a matter of the problems we had in ujicobakanfirst. Based on the analysis of data obtained with a significance level of 0.05, on to the significance of 0.000 Â 0.05 means that Â rejected the conclusions that can be drawn dalah mathematical communication skills of students usingmethod Reciprocal Teaching is better than the mathematical communication skills using methods expository.